Sexual and Reproductive Health Education: A Case Study at Pembina Pekanbaru Special School - Prawira, Arif; Aprilia, Imas Diana (Journal of ICSAR, 2024)
The easy access to inappropriate content through digital media presents a particular challenge in education, particularly in special education. This research aims to get a better understanding of sexual and reproductive health education at the Pembina Pekanbaru Special School, Indonesia. The method of this research uses a qualitative method, and the data is collected through interviews with 4 teachers and 2 parents of students. The results indicate that sexual and reproductive health education at the school is still limited to aspects of the content of human anatomy and physiology. However, other aspects such as sexual and reproductive health are not given sufficient attention. Factors that contribute to the limitations of the learning process at the school such as a lack of resources, poorly structured curricula, and inadequate training for teachers. Therefore, more coordination and comprehensive efforts are needed to improve sexual and reproductive health education for students with special needs at the school.